LEFT VENTRICULAR HYPERTENSION IN CARDIOLOGY (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Left ventricular hypertension (LVH) is a pathological condition associated with an increase in the activity or tension of the left ventricle of the heart, which has a negative effect on the normal functioning of the heart. This condition usually occurs as a result of high blood pressure, heart valve disease, or other heart conditions. Left ventricular hypertension can cause heart failure, shortness of breath, fatigue and other clinical symptoms. The diagnosis is made using tools such as echocardiography and electrocardiogram. Treatment is mainly through medication and lifestyle changes, which help improve the patient's health. Timely detection and treatment are important in the management of this disease.